Leveraging Electronic Word of Mouth for Promoting Sustainable Tourism: Insights from Bali and Lombok Travel Agents - Surayyal Hizmi; Endang Sri Wahyuni; Jumraidin; Nawawi (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This investigation examines the significance of Electronic Word of Mouth (eWOM) in facilitating sustainable tourism by scrutinizing the digital marketing methodologies and operational practices of Lombok Hidden Trip and Goodfriend Travel in the regions of Bali and Lombok. Although eWOM has been established as an influential mechanism in shaping traveler behavior, its strategic deployment in the context of sustainable tourism marketing is yet to be thoroughly investigated. This research seeks to bridge this gap by evaluating both agencies' adherence to the standards set forth by the Global Sustainable Tourism Council (GSTC) through semi-structured interviews, analysis of social media content, and operational assessments. The findings reveal that Lombok Hidden Trip exhibits a robust commitment to environmental sustainability, integrating eco-tours, initiatives for reusable resources, and proactive engagement on social media platforms. Conversely, Goodfriend Travel prioritizes the preservation of cultural heritage, providing Balinese culinary workshops and traditional rituals; however, it lacks a coherent strategy for the effective utilization of eWOM. Despite their respective contributions, both agencies encounter significant challenges, such as constrained financial resources, inadequate visitor awareness, and a lack of systematic monitoring of sustainability practices. To optimize sustainability outcomes, this study advocates that Goodfriend Travel enhance its eWOM engagement strategies, while Lombok Hidden Trip should broaden its sustainability initiatives. Furthermore, both agencies are encouraged to implement visitor education programs, conduct systematic sustainability audits, and provide training for staff to improve adherence to GSTC standards. This investigation highlights the transformative potential of eWOM in promoting responsible tourism and provides actionable insights for travel agencies, policymakers, and tourism stakeholders to advance environmental, cultural, and social sustainability in the regions of Bali and Lombok.